1992
DOI: 10.1177/002199839202601001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Longitudinal Splitting on Tensile Strength of Unidirectional Aramid Fiber Reinforced Plastics

Abstract: An increase in aramid SVM (trademark of polyparaamidobenzimidazole fiber) content up to 85 vol. % leads to an increased tensile strength of the composite. An increase in fiber content, V f , leads to a change of the fracture mode from fiber control at low V f to matrix and matrix/interface dominated longitudinal splitting of the composite at high V f . The correlation between transverse properties and longitudinal tensile strength of different aramid fiber reinforced plastics was investigated. Longitudinal spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The tensile strength in the fiber direction (0 • ) is shown in Figure 5c, compared to published strengths for traditional aramid/epoxy composites [40,48,49]. While the strength is lower than what can be achieved with traditional composites, the published results show that this can largely be caused by the presence of voids surrounding the fibers and a lack of optimized fiber sizing [49,51,52].…”
Section: Tensile Testingmentioning
confidence: 95%
See 1 more Smart Citation
“…The tensile strength in the fiber direction (0 • ) is shown in Figure 5c, compared to published strengths for traditional aramid/epoxy composites [40,48,49]. While the strength is lower than what can be achieved with traditional composites, the published results show that this can largely be caused by the presence of voids surrounding the fibers and a lack of optimized fiber sizing [49,51,52].…”
Section: Tensile Testingmentioning
confidence: 95%
“…(c) The tensile strength of UD 0 • printed aramid/PETG composites increases linearly with added fiber volume content. Comparison to traditional aramid/epoxy composites shows lower-than-expected strength, and results from literature show that the lack of sizing can cause this drop [40,48,49]. (d) The tensile strength of UD 90 • printed aramid/PETG composites compared to a non-reinforced 3D-printed PETG sample.…”
Section: Tensile Testingmentioning
confidence: 99%
“…35 In the third step, isolated, multiple carbon fiber fractures and longitudinal splitting events connect, resulting in final fracture of the CFRP in the fourth step. 37,38 Thus, transverse compressive stress can influence the fracture behavior of a CFRP. Transverse compressive stress is calculated in the following section to predict the mechanical behavior of CFRP/steel hybrid laminates.…”
Section: Modeling Approachmentioning
confidence: 99%
“…Work by Kortschot et al [6] on notched crossply CFRP laminates indicated a similar relationship for split growth and that split length/notch length ratio was proportional to the square of the applied stress. Whilst the resistance of carbon [3] and glass [7] FRP composites to splitting along the fibres is similar for static loading the behaviour of aramid fibre composites appears to be controlled by different mechanisms [8].…”
Section: Introductionmentioning
confidence: 99%